Yearbook of Muslims in Europe. - Scharbrodt, Oliver.; Akgönül, Samim. (Yearbook of Muslims in Europe, 2016)
Now in a new format with a more current and topical focus on a country level. While the strength of the Yearbook has always been the comprehensive geographical remit, starting with volume 7 the reports primarily concentrate on more specific and topical information. The most current research available on public debates, transnational links, legal or political changes that have affected the Muslim population, and activities and initiatives of Muslim organizations from surveyed countries are available throughout the Yearbook. At the end of each country report, an annual overview of statistical and demographic data is presented in an appendix. By using a table format, up-to-date information is quickly accessible for each country. To see how these changes affect the articles, please read this sample chapter about Austria. The Yearbook of Muslims in Europe is an essential resource for analysis of Europe's dynamic Muslim populations. Featuring up-to-date research from forty-six European countries, the reports provide cumulative knowledge of on-going trends and developments around Muslims in different European countries. In addition to offering a relevant framework for original research, the Yearbook of Muslims in Europe provides an invaluable source of reference for government and NGO officials, journalists, policy-makers, and related research institutions.